The Effect of Strategic Human Resource Management on Organizational Performance with Organizational Commitment as a Mediating Variable at Sada Organizer in Padang City - Kholilul Kholik; Bambang Pramono; Hilfan Helmy; Anton Sobirin; Ardani Putra Yudha (International Journal of Management, Economic and Accounting, 2026)
Strategic human resource management is an important factor for service organizations because service success depends heavily on employee competence, commitment, and work behavior. This study aims to analyze the effect of strategic human resource management on organizational performance with organizational commitment as a mediating variable at Sada Organizer in Padang City. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees involved in operations, client services, event coordination, and organizational administration. Data were analyzed using Partial Least Squares Structural Equation Modeling. The results show that strategic human resource management has a positive and significant effect on organizational commitment. Strategic human resource management also has a positive effect on organizational performance. Furthermore, organizational commitment has a positive effect on organizational performance and mediates the relationship between strategic human resource management and organizational performance. These findings indicate that well-directed HR practices, such as needs-based recruitment, employee training, reward systems, performance appraisal, and career development, can improve organizational performance when they strengthen employee commitment. This study implies that Sada Organizer needs to enhance strategic HR management to improve service quality, work coordination, and sustainable organizational achievement.